Emissions from prescribed burning of agricultural fields in the Pacific Northwest. (October 2017) - Holder, A.L.; Gullett, B.K.; Urbanski, S.P.; Elleman, R.; O'Neill, S.; Tabor, D.; Mitchell, W.; Baker, K.R.
Abstract: Prescribed burns of winter wheat stubble and Kentucky bluegrass fields in northern Idaho and eastern Washington states (U.S.A.) were sampled using ground-, aerostat-, airplane-, and laboratory-based measurement platforms to determine emission factors, compare methods, and provide a current and comprehensive set of emissions data for air quality models, climate models, and emission inventories. Batch measurements of PM2.5, volatile organic compounds (VOCs), polycyclic aromatic hydrocarbons (PAHs), and polychlorinated dibenzodioxins/dibenzofurans (PCDDs/PCDFs), and continuous measurements of black carbon (BC), particle mass by size, CO, CO2, CH4, and aerosol characteristics were taken at ground level, on an aerostat-lofted instrument package, and from an airplane. Biomass samples gathered from the field were burned in a laboratory combustion facility for comparison with these ground and aerial field measurements. Emission factors for PM2.5, organic carbon (OC), CH4, and CO measured in the field study platforms were typically higher than those measured in the laboratory combustion facility. Field data for Kentucky bluegrass suggest that biomass residue loading is directly proportional to the PM2.5 emission factor; no such relationship was found with the limited wheat data. CO2 and BC emissions were higher in laboratory burn tests than in the field, reflecting greater carbon oxidation and flaming combustion conditions. These distinctions between field and laboratory results can be explained by measurements of the modified combustion efficiency (MCE). Higher MCEs were recorded in the laboratory burns than from the airplane platform. These MCE/emission factor trends are supported by 1–2 min grab samples from the ground and aerostat platforms. Emission factors measured here are similar to other studies measuring comparable fuels, pollutants, and combustion conditions. The size distribution of refractory BC (rBC) was single modal with a log-normal shape, which was consistent among fuel types when normalized by total rBC mass. The field and laboratory measurements of the Angstrom exponent (α) and single scattering albedo (ω) exhibit a strong decreasing trend with increasing MCEs in the range of 0.9–0.99. Field measurements of α and ω were consistently higher than laboratory burns, which is likely due to less complete combustion. When VOC emissions are compared with MCE, the results are consistent for both fuel types: emission factors increase as MCE decreases. Graphical abstract: Highlights: Emissions from prescribed fires of agricultural fields were measured. VOCs, PAHs, PCDDs/PCDFs, PM2.5 and aerosol characteristics were analyzed. PM2.5 emission factors were directly proportional to grass residue loading. VOC emission factors were related to modified combustion efficiency. Airplane-, laboratory-, ground-, and aerostat-based platforms determined emissions.